1991
DOI: 10.3109/10915819109078651
|View full text |Cite
|
Sign up to set email alerts
|

Toxicologic Evaluation of Cellulon™ Fiber; Genotoxicity, Pyrogenicity, Acute and Subchronic Toxicity

Abstract: CellulonTM fiber, a cellulose produced by a bacterial fermentation process employing a strain of Acetobacter aceti subsp. xylinum, was tested for genotoxicity in four assays: (1) microbial reverse mutation assay in Salmonella typhimurium (Ames assay), (2) an assay for chromosomal aberrations in Chinese hamster ovary (CHO) cells, (3) an assay for induction of unscheduled DNA synthesis (UDS) in rat primary hepatocytes, and (4) the CHO/HGPRT forward mutation assay. Each assay was conducted at a wide range of dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 8 publications
3
23
1
Order By: Relevance
“…Increased cecum weights in this study was considered a physiological adaptation related to the ingestion of large amounts of modified starch, fibrous ingredients, or other carbohydrates which are poorly absorbed and have a high osmotic nature (Leegwater et al, 1974;Newberne et al, 1988;Trout et al, 1983;Yoshioka et al, 1994). The reason for the difference from previous reports that increased cecal weights were not evident in rats fed fermentation-derived cellulose or microcrystalline cellulose at dietary levels up to 10% (JECFA, 1998;Schmitt et al, 1991) remains unclear.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Increased cecum weights in this study was considered a physiological adaptation related to the ingestion of large amounts of modified starch, fibrous ingredients, or other carbohydrates which are poorly absorbed and have a high osmotic nature (Leegwater et al, 1974;Newberne et al, 1988;Trout et al, 1983;Yoshioka et al, 1994). The reason for the difference from previous reports that increased cecal weights were not evident in rats fed fermentation-derived cellulose or microcrystalline cellulose at dietary levels up to 10% (JECFA, 1998;Schmitt et al, 1991) remains unclear.…”
Section: Discussioncontrasting
confidence: 53%
“…Fermentation-derived cellulose has been eaten for many years as a dessert food called "nata" or "nata de coco" in the Philippines (Omoto et al, 2000). It is reported to lack genotoxicity, pyrogenicity and acute or subchronic toxicity (Schmitt et al, 1991). Fermentation-derived cellulose is generally accepted to be safe for eating or drinking and is used as a food additive in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…BC has unique characteristics including high purity, high crystallinity and remarkable mechanical properties, due to the uniform ultrafine-fibre network structure, the high planar orientation of the ribbon-like fibres when compressed into sheets, the good chemical stability, and the high water holding capacity (Svensson et al, 2005). Several materials based on bacterial cellulose, recognized as non-genotoxic and noncytotoxic, have been commercialized (Schmitt et al, 1991;Jonas and Farah, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, although in vivo studies demonstrate the BC biocompatibility , and lack of mutagenicity (Schmitt et al, 1991), no reports are available on the BC nanofibres toxicity. Although BC is not expected to be degraded in vivo, safety concerns makes this study mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the non-toxicity and non-mutagenicity enable microbial cellulose to be a popular candidate for wound healing dressings and tissue engineering scaffolds [7][8][9][10][11]. For example, Klemm et al reported using bacterial cellulose for temporary substitutes for skin and artificial blood vessels [12].…”
Section: Introductionmentioning
confidence: 98%